The politics of crime in interwar England and Wales: with particular reference to some discontinuities with nineteenth century criminal justice policy - Taylor, Howard (1997)
This thesis seeks to place in a political context interwar developments in criminal justice policy. The first part takes issue with the dominant position of much of the traditional historiography that crime was not a political issue. Instead, it argues, both at a 'high' political level and at the level of 'low' politics, criminal justice was always intensely political. The second and third parts of the thesis seek to recontextualize the history of criminal justice between the nineteenth and mid-twentieth centuries. In particular, statistical evidence is used to argue that criminal justice was supply-led and not demand-led. In other words crime, including murder, was budgeted and rationed by managers. Part II examines the connections between the public cost of prosecutions, the emergence of the new police, and the introduction of the new series of criminal statistics after the mid-nineteenth century. The final part of the thesis explores the effect escalating police costs and intense public parsimony had on criminal justice after the First World War. It argues that in a significant number of areas this period was fundamentally discontinuous with the earlier period. The conclusion raises basic issues concerning the methodology of some of the social sciences, the nature of British democracy, and suggests that a far more critical approach should be adopted by researchers towards official rhetoric and, in particular, towards official statistics.